Genetic differences in CYP2C19 single nucleotide polymorphisms among four Asian populations - Yamada S. (2014)
Background. This study was designed to compare genetic differences in single-nucleotide polymorphisms of the S-mephenytoin 4′-hydroxylation (CYP2C19) gene among four Asian populations. Methods. Polymerase chain reaction with restriction fragment length polymorphism (PCR-RFLP) analysis of CYP2C19 was conducted in Japanese, Chinese, Thai, and Vietnamese populations. All genotype frequencies were analyzed. Wild-type homozygote and wild-type heterozygote genotypes were extensive proton pump inhibitor (PPI) metabolizers. Mutant-type heterozygote and mutant-type homozygote genotypes were poor PPI metabolizers. Results. No significant differences in CYP2C19 phenotype, calculated based on genotype frequencies, (P > 0.05) were found among the four populations. Conclusions. Many factors, including CYP2C19 polymorphisms, affect the success rate of Helicobacter pylori eradication with PPI-based therapy. We suspect that CYP2C19 polymorphisms may not be the main factor associated with differences among these four Asian populations in the success rates of H. pylori eradication with PPI-based therapy.